Quercetin isolated from Hedysarum neglectum Ledeb. as a preventer of metabolic diseases - Anna D. Vesnina; Irina S. Milentyeva; Violeta M. Le; Anastasiya M. Fedorova; Olga G. Altshuler; Alexander Yu. Prosekov (Foods and Raw Materials, 2025)
Diseases associated with metabolic disorders seem to affect more and more people worldwide. Biologically active supplements may prevent or relieve metabolic disorders. Quercetin is known for its potential to inhibit metabolic syndrome. This paper introduces an in vivo experiment on rodents. It featured hypoglycemic, hypocholesterolemic, and hepatotoxic properties of quercetin. Quercetin was obtained from the hairy root extract of Hedysarum neglectum Ledeb. Two doses (50 and 100 mg/kg) were used to evaluate its hypoglycemic potential. Rats with induced diabetes were tested for body weight, glucose, and cholesterol while mice with induced hypercholesterolemia were checked for blood cholesterol changes. Potential biochemical and pathological changes in the liver were also studied on rats. Quercetin treatment caused neither significant health problems nor death in the model animals. It had no effect on body weight, even in the animals with induced diabetes. In addition, quercetin did not increase glucose and cholesterol in the blood and triggered no pathological changes in the liver. Quercetin isolated from H. neglectum hairy root extract demonstrated no hepatotoxicity. Unfortunately, it showed no beneficial effect on cholesterol and glucose levels and had no efficacy against metabolic syndrome. Further research is needed to assess the effect of quercetin on other metabolic markers, e.g., genes associated with the metabolism of lipids, carbohydrates, etc.